CARICATURE OF INDIA OTHER HALF OF THE XIX CENTURY - Горбачова, В. В.; Соколюк, Л. Д. (Art and Design, 2023)
Purpose: analyze the caricature of India in the second half of the 19th century, to determine its influence on the consciousness of society and to clarify the thematic and plot features and pictorial techniques. Methodology. General scientific methods of analysis and synthesis, induction, and deduction, as well as historical and cultural, art history and comparative methods are used. The results. The caricature of India of the second half of the 19th century was studied in its satirical magazines. The prerequisites for the appearance of such publications and their connection with the development of similar periodicals in Europe and certain socio-cultural features of colonial policy in India are revealed. The leading satirical publications («Delhi Sketch Book», «Indian Charivari», «Basantaka», «Hindu Punch», etc.) are briefly characterized. The history of the development and functions of the Indian caricature of the stated period is highlighted. It has been revealed that the thematic and plot features of the Indian caricature of this era are caused by social unrest associated with the oppression of Hindus by the colonial authorities, their struggle for political freedoms and the development of national artistic culture. Individual caricatures are analyzed with an overview of the historical and regional context and the pictorial techniques used by the authors. Scientific novelty. For the first time in Ukrainian art history, a review of Indian illustrated publications that produced caricatures of the current issues of Indian cultural revival is presented, which is important for the further development of the Oriental studies direction in Ukraine Practical significance. The results of the research can be used in lecture materials related to the topic of the history of caricature and will also serve the museum study and the development of Indology in Ukraine.